Hope for the Future: Key Informants' Perspectives on HIV Prevention in Dominican Republic Batey Communities: A Qualitative Descriptive Study - Filiau, Alaina; Boucher, Jean; Pugnaire, Michele; Casimir, Tara (The Journal of the Association of Nurses in AIDS Care, 2025)
Supplemental Digital Content is Available in the Text. AbstractThe purpose of our study was to understand the interlocking spheres of cultural identity and health behaviors related to HIV prevention within Haitian migrant batey communities in La Romana, Dominican Republic. A qualitative description design was employed using the PEN-3 model by Airhihenbuwa (1990) as a theoretical framework. Data were collected through semi-structured interviews with 12 key informants. Participants, primarily adults of Hispanic (10) and African descent (2), ranged from 33 to 53 years old, with a majority having high school or higher education. A central theme, "Hope for the Future," emerged, highlighting five subthemes: stigma/discrimination, religious beliefs, voodoo tenets, community nurturers, and HIV education. Findings emphasized the need for a multifaceted approach using community health workers and incorporating local cultural contexts, including religious beliefs and stigma, to enhance HIV prevention efforts. Cultural identity of Haitian migrant batey communities included religious beliefs, stigma, and cultural practices as considerations in HIV prevention interventions.